Comparative effectiveness of school-based caries prevention: a prospective cohort study - Ryan Richard Ruff; Richard Niederman (BMC, 2018)
Abstract Background Dental caries is the world's most prevalent childhood disease. School-based caries prevention can reduce the risk of childhood caries by increasing access to care. However, the optimal mix of treatment services, intensity, and frequency of care is unknown. Methods Data were derived from two prospective cohorts of US children participating in two caries prevention programs with different treatment intensities. One program provided primary and secondary prevention (glass ionomer sealants and interim therapeutic restorations) and one primary prevention only (glass ionomer sealants), both given twice yearly in six-month intervals. Primary study outcomes included untreated decay and the total observed caries experience. Analysis used generalized additive models to estimate nonlinear effects and trends over time. Results were compared to those estimated using generalized estimating equations and mixed-effects multilevel Poisson regression. Results Primary and secondary prevention combined did not significantly reduce total caries experience compared to primary prevention alone, but did reduce the risk of untreated decay on permanent dentition. Additionally, the rate of new caries experience was slower in the primary and secondary prevention group. Nonlinear trends for dental caries across both programs were statistically significant from zero (p < .001). Conclusion Caries prevention consisting of primary and secondary prevention agents may be more effective than primary prevention alone in reducing the risk of tooth decay over time. Results suggest that the impact of caries prevention may not be constant over the medium- and long-term, suggesting reduced effectiveness with continued treatments.